Balint groups with junior doctors: a systematic review. Issue 3 (2nd July 2020) - Salter, Emma; Hayes, Adrian; Hart, Roxanne; Orrell, Rose-Anne; Jameson, Joseph; Knight, Christopher; Pickhaver, Jenny; Baverstock, Anna
Abstract : This paper aims to explore the use of Balint Groups amongst doctors in training. Reviews published to date have explored the use and effects of Balint groups in general and specifically with medical students, but not solely medical trainees. A systematic review was conducted, with the following data bases searched: Medline, Embase, Cochrane and PsychINFO. Articles met inclusion criteria if they presented empirical research using quantitative and qualitative methodology, involved junior doctors participating in groups and were written in English. No publication date limit was set. 817 articles were screened after de-duplication. 52 full articles were reviewed for eligibility. 27 articles met inclusion criteria. 12 articles included quantitative data, ten qualitative and five contained both qualitative and quantitative data Seven papers involved pre- and post-group data collection, six studies involved comparison groups, seven discussed group processes, six discussed trainee experience and four discussed topic themes. The literature published is heterogenic in methodology, and outcome measures differ widely. Feasibility of running groups and benefits to participants are not clearly evidenced. The authors discuss findings of the literature and explore possible personal and educational effects of Balint groups on trainees, and feasibility of running such groups in this cohort.